Learning design to develop 21st century competencies for students in small private school in southernmost provinces of Thailand - SONGMUANG, JARUWAT; อัซซอลีฮีย์ มูฮัมหมัดอาฟีฟี; โต๊ะตาหยง อภิรักษ์; มันยูนุ มูฮามัสสกรี; ดือรามะ มะยูตี; จ๊ะนุ อิลฮาม (Al-HIKMAH Journal, 2024)
The IIIP Model is a teaching model developed through participatory action research among secondary school teachers in private schools in the southernmost provinces of Thailand. Aimed to promote students’ learning and determination skills, develop and construct readiness regarding competencies in the 21st century for students in private schools in the southernmost provinces, which has 4 elements: inspiration, information management, implementation and progress. The results of learning management with the IIIP model affect to develop 3 important competencies: 1) learning skills and innovation ; students have clear learning goals from adapting learning problems from daily life and make students to develop concrete pieces of work from their learning. 2) Information Literacy, Media and technology skills where students can search for information and develop work pieces by using information technology by themselves; and 3) life and career skills ;students have creativity, responsibility for themselves and society, Behave as a good Muslim.